Abstract Presentation at Two Veterinary Surgery Conferences and the Impact on Publication Rate - Kettleman, William S.; Torres, Bryan T. (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Objectives The aim of this study was to compare the publication rate (PR) and report descriptive findings from abstracts presented at the American College of Veterinary Surgeons (ACVS), the Veterinary Orthopaedic Society (VOS), and those presented at both conferences.Study Design All conference abstracts from 2001 to 2010 ACVS and VOS meetings were reviewed. PR in peer-reviewed journals was evaluated and compared between Group 1 (abstracts presented at ACVS only; n = 1,277), Group 2 (abstracts presented at VOS only; n = 645), and Group 3 (abstracts presented at both conferences; n = 121) abstracts. Abstracts were assigned a level of evidence (LoE) score.Results Approximately 6% of all abstracts evaluated were presented at two scientific meetings (Group 3). The PR of Group 1 (66%) and Group 3 (62%) abstracts was significantly higher than that of Group 2 (45%). The majority of abstracts were assigned a low LoE (3 or 4). Once presented, most Group 3 abstracts took <12 months to be submitted and <24 months to be published.Conclusion This study found that a limited number of abstracts were presented at both ACVS and VOS, and PR was significantly different between those presented at ACVS only or both ACVS and VOS compared with VOS only. There was no significant difference in PR between Group 1 and Group 3 abstracts. This study has provided the initial comparison between abstracts presented at two veterinary surgical conferences.
Keywords: abstracts; duplicate presentations; level of evidence; publication rate